FERMAT TEST AND THE EXISTENCE OF PSEUDOPRIMES - Ega Gradini (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2011)
In this paper the author present Fermat test as one of primality tests. In order to perform the ability of the test, the algorithm of the test coded in Mathematica (6.0 version). The application of Fermat’s Little Theorem as well as Euler’s Theorem on the tests are also discussed and this leads to the concept of pseudoprime.